Patterns of postprandial hyperglycemia after basal insulin therapy: individual and regional differences. Issue 3 (18th November 2014) - Shaefer, Charles; Reid, Timothy; DiGenio, Andres; Vlajnic, Aleksandra; Zhou, Rong; Ameer, Barbara; Riddle, Matthew
Abstract Background Treatment of postprandial hyperglycemia could be needed when basal insulin added to oral therapy does not maintain glycated haemoglobin (HbA1C) targets in type 2 diabetes mellitus. Knowing individual and regional patterns of postprandial hyperglycemia in this setting might improve therapeutic decisions. Methods Patient‐level self‐monitored blood glucose data were pooled from six studies of insulin glargine for patients with HbA1C ≥ 7.0% after 24 weeks. Percentages of participants with highest daily postprandial blood glucose and greatest postprandial increments after each of the three daily meals were calculated and compared between four geographical regions; USA, Canada, Germany, and other European countries. Results For 494 participants (mean age 60.1 years, diabetes duration 9.6 years, and BMI 29.8 kg/m2), mean endpoint HbA1C was 7.8%. On insulin glargine treatment, highest postprandial blood glucose most often occurred post‐dinner (44% of participants) and greatest postprandial increments post‐breakfast (46% of participants) in all regions. Participants with greatest postprandial increments post‐breakfast were older and experienced less HbA1C improvement with insulin glargine than those with greatest postprandial increments after other meals. Post‐breakfast and post‐dinner postprandial blood glucose was higher in the USA and Canada versus Germany, and in the USA versus Other European countries (all p < 0.05). Postprandial increments after dinner were greater in the USA versus all other regions. Conclusions Generally, highest postprandial blood glucose follows dinner and greatest postprandial increments follow breakfast. Variations in patient characteristics and eating patterns might underlie differences both within and between regions. Awareness of regional differences and evaluation of an individual's typical eating pattern might facilitate appropriate prandial therapy. Copyright © 2014 John Wiley & Sons, Ltd.